Commentary - Hanssmann, Fred (Management Science, 1965)
Comments about Churchman, C. W., A. H. Schainblatt. 1965. The researcher and the manager: A dialectic of implementation. Management Sci. 11 (4) B-69–B-87. The purpose of this paper is to review various opinions and differences of opinion which have been expressed concerning that aspect of research referred to as “implementation.” We have used the term “implementation” to refer to the manner in which the results of scientific effort may come to be used by the manager. The “problem of implementation” is the problem of determining what activities of the scientist and the manager are most appropriate to bring about an effective relationship between the two.